Spatiotemporal distribution dynamics of elephants in response to density, rainfall, rivers and fire in Kruger National Park, South Africa. Issue 6 (27th February 2019) - MacFadyen, Sandra; Hui, Cang; Verburg, Peter H.; Van Teeffelen, Astrid J. A.
Abstract: Aim: African elephants are ecosystem engineers. As such, their long‐term patterns of distribution and abundance (i.e., space‐use intensity) will influence ecosystem structure and function. We elucidate these patterns for bull versus herd groups, by analysing the spatiotemporal dynamics of an increasing elephant population in relation to key ecological drivers: rainfall, distance to major rivers and time since last fire. Significant changes to the long‐term patterns of elephant density and group‐type probabilities are identified and explained. Location: Kruger National Park, South Africa. Methods: Using almost three decades of census records (1985–2012), we applied Multiple Point Process Models to assess the influence of rainfall, rivers and fire in shaping elephant space‐use. Significant changes to the long‐term patterns of elephant density and group type were also identified using kernel density estimates and the spatially varying probability of encountering either bull or herd group. Results: Bull and herd groups are no longer clearly segregated as available empty space becomes more limited. Bull and herd groups have dichotomous resource selection functions, in that bulls concentrate in areas receiving lower rainfall but more frequent fires while herds concentrate in higher rainfall areas experiencing less frequent fires. Both bull and herd groups concentrate closer to major rivers, emphasizing rivers as important spatial drivers. Overall, densities increased most significantly closer to rivers and in areas experiencing fewer fires. Fire was also a strong agent of group‐type change, as the probability of finding bulls, contrary to herds, significantly increased as fire return periods shortened. Main conclusions: Elephant distribution and abundance patterns have homogenized in response to increased space limitations, with group‐specific, fire‐driven distribution patterns emerging overtime. Results herein should be used to help manage elephant space‐use through the establishment of possible refuge areas and the development of more empirical research into elephant impacts in future.